Partitioning carbon fluxes in a permafrost landscape - Eckhardt, Tim (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
Arctic tundra ecosystems have acted as a historical sink for atmospheric carbon (C). Therefore, these ecosystems contain significant amounts of carbon in their frozen soils and sediments. The function as strong C sink is a product of short summers, low temperatures, well-adapted vegetation and water saturated conditions, which causes low degradation and mineralization rates of soil organic matter (SOM). The Arctic is currently facing amplified climate warming and the rate of this warming is expected to accelerate. A number of changes are predicted in response to warming. On the one hand, warming is expected to cause the deeper thaw of permafrost affected soils leading to both the enhanced production of carbon dioxide (CO2) due to the increasing degradation of SOM, and increased methane (CH4) formation, which could create a positive climate feedback to global warming. On the other hand, due to higher temperatures the assimilation of CO2 by vegetation will increase. Therefore, it remains uncertain how the C sink function of arctic tundra landscapes will react to future changes in climate. This study aimed to determine the CO2 and CH4 fluxes at the soil-plant-atmosphere interface in an arctic tundra ecosystem and to identify the main environmental drivers of these fluxes. Furthermore, as the processes governing CO2 net ecosystem exchange (NEE) react differently on a changing climate, the CO2 fluxes were partitioned into gross primary productivity (GPP) and ecosystem respiration (Reco). Reco was further partitioned into its autotrophic (RA) and heterotrophic respiration (RH) components. The study was conducted using chamber measurements on the microscale (1 m – 10 m) in a polygonal tundra environment in the Lena River Delta in 2014 and 2015. In order to estimate the CO2 fluxes over the complete growing season in 2015, they were reproduced using flux models. This work finds the polygonal tundra in the Lena River Delta to be a robust sink for atmospheric CO2 and a source for CH4. The CO2 sink strength was highly ...